Case Report: A New Perspective of Aging Disease of the Eye - FNMI, Noor; R, Abdul Hadi (International Journal of Human and Health Sciences (IJHHS), 2024)
Fuch’s endothelial dystrophy (FED) is one of the causes of gradual onset vision loss in adults. It is a hereditary autosomal dominant genetic disease affecting the cornea whereby the chance of inheriting a mutated gene is 50%. An adult with FED may be asymptomatic at a young age but later present with progressively worsened vision loss. We presented a case of a 69-year-old gentleman with no known medical illness who complained of progressive reduced vision and watery eyes of the left eye for one month. He had a history of left eye uncomplicated phacoemulsification surgery with posterior chamber intraocular lens three years ago in another private hospital. Post-surgery, he had good vision over the left eye. On ocular examination, the best corrected visual acuity in the right eye was 6/60 and hand movement (HM) in the left eye. Intraocular pressure was normal bilaterally. Anterior segment examination of the left eye revealed diffused corneal edema with multiple epithelial bullae inferiorly. The examination of the right eye was normal. Pachymetry and specular microscopy confirmed the diagnosis of left eye decompensated FED. He underwent left eye optical penetrating keratoplasty and is currently under Ophthalmology clinic follow-up for visual recovery. Patients with FED are usually diagnosed at a later age. Some patients may also have coexisting cataracts with FED. In relation to this case, he was diagnosed with decompensated FED after undergoing phacoemulsification for cataract removal. We highlight the importance of careful ocular evaluation as a precaution prior to the cataract surgery to avoid the risk of decompensated corneal injury due to FED. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S33